A Very Rare Case of Expanded Dengue Syndrome with Acute Liver Failure, Rhabdomyolysis, Acute Kidney Injury and ARDS: Successfully Treated with Haemoadsorption, Hemodialysis, and Plasma Exchange - Mithun Kumar Mondal; Dilruba Akhter Jima; Sadat Bin Siraj (Bangladesh Critical Care Journal, 2025)
Expanded dengue syndrome, accompanied by liver failure, rhabdomyolysis, acute kidney injury, and severe acute respiratory distress syndrome (ARDS), represents a highly lethal condition with a significantly elevated mortality rate. Conventional treatments are ineffective in addressing all these complications concurrently. This case report discusses a young male patient who underwent haemoadsorption, hemodialysis, and subsequently plasma exchange. The patient achieved full recovery without any residual impairment. This report presents the first instance of a dengue patient undergoing simultaneous haemoadsorption and hemodialysis, followed by plasma exchange. Bangladesh Crit Care J March 2025; 13 (1): 51-55